Halogenated phenazinothiadiazoles: electron transporting materials [data] - Zong, Wansheng; Hippchen, Nikolai; Dittmar, Benedikt; Elter, Maximilian; Ludwig, Philipp; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Universität, 2024)
Triisopropylsilyl-(TIPS)-alkynylated phenazinothiadiazoles were prepared by the condensation of halogenated ortho-quinones and TIPS-alkynylated 5,6-diamino-2,1,3-benzothiadiazole with different combinations of halogen substituents. The compounds pack in brickwall motif of head-to-head dimers featuring intermolecular S-N contacts and short π-π distances, suggesting their suitability as n-channel materials in organic thin film transistors. The halogenated phenazinothiadiazoles show electron mobilities μmax ranging between 0.14 cm2V-1 s-1 and 0.76 cm2 V-1 s-1.
Gefördert durch: Deutsche Forschungsgemeinschaft: INST40/575-1FUGG, Deutsche Forschungsgemeinschaft: SFB 1249
Gesehen am 14.03.2024
Keywords: Forschungsdaten; Datenbank